Treating full-thickness cuff tears in the athlete: Advances in arthroscopic techniques - Park, M. C.; El Attrache, N. S. (Clinics in Sports Medicine, 2008)
Full-thickness rotator cuff tears in the athlete generally occur from either high-energy contact or repetitive overhead activity. Surgical management of these injuries with a technique that maximizes footprint contact while providing a gap-resistant repair may enhance an optimal healing environment. The elite overhead athlete with a full-thickness tear has a relatively poor prognosis, and requires special consideration.